PENGARUH BUDAYA DAN KELUARGA TERHADAP MINAT MENABUNG NASABAH DI BANK SYARIAH - RONI ANDESPA (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The research theme is the concept of business According to Islamic economics. The objectives of the research are: to see the influence of culture and family on the interest of saving customers. The research variables are: 1. Family, 2. Culture, and 3. Interest Saving. Hypothesis1: There is a significant influence between cultures (X1) with interest in saving (Y). 2. Hypothesis2: There is a significant influence between family (X2) with interest in saving (Y). The object of research is Islamic Bank in West Sumatra. The type of research is causality research with quantitative approach. The research population is all Islamic banking customers in West Sumatera. The sample of research is as many as 250 customers. The technique in sampling is non probability sampling method. Data analysis using multiple linear regression analysis. The results found that culture and family significantly affected the interest of saving Islamic bank customers.